2014
DOI: 10.1194/jlr.m053124
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin induces bile acid-synthetic enzyme Cyp7a1 by suppressing FXR signaling in both liver and intestine in mice

Abstract: This article is available online at http://www.jlr.orgStatins are a class of drugs that are used to lower cholesterol levels by specifi cally inhibiting HMG-CoA reductase, which is the rate-limiting enzyme in cholesterol biosynthesis in the liver. Statins reduce LDL (bad cholesterol) as much as 20-60%, lower triglycerides, and slightly increase HDL (good cholesterol) ( 1, 2 ). Therefore, statins are used as the most effective drugs for treating CVDs. Commercially available statins include atorvastatin (Lipitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
46
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 56 publications
12
46
2
1
Order By: Relevance
“…Cholic acid (CA) and chenodeoxycholic acid (CDCA) (and muricholic acids in mice), are primary BAs. Some secondary BAs include deoxycholic acid (DCA), LCA, and ursodeoxycholic acid (UDCA) (32). …”
Section: Gut Bacterial Metabolites Co-metabolites and Other MImentioning
confidence: 99%
See 1 more Smart Citation
“…Cholic acid (CA) and chenodeoxycholic acid (CDCA) (and muricholic acids in mice), are primary BAs. Some secondary BAs include deoxycholic acid (DCA), LCA, and ursodeoxycholic acid (UDCA) (32). …”
Section: Gut Bacterial Metabolites Co-metabolites and Other MImentioning
confidence: 99%
“…We have several publication demonstrating that BA homeostasis can be affected by various factors, such as age (30, 33), gender (30), diet (34, 35), and drugs (32). Disruption of the enterohepatic circulation of BAs can give rise to cholestasis and NAFLD, which may progress to fibrosis and cirrhosis.…”
Section: Gut Bacterial Metabolites Co-metabolites and Other MImentioning
confidence: 99%
“…Hydrophobic BAs are potent inflammatory chemical that cause injury to liver (Chiang 2013). In vitro and in vivo studies indicate that statins can alter BA metabolism in hepatocytes (Byun et al 2014;Fu et al 2014). The rate-limiting enzyme for the classic pathway of BA synthesis in the liver is Cyp7a1 (Chiang 2013).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…Grapeseed proanthocyanidin has also been found to enhance the excretion of bile acid by up-regulating CYP7A1 but lowering the expression of LXRα in hamsters (Jiao et al, 2010). Some previous studies demonstrated that other receptors, such as farnesoid X receptor (FXR) and PPARγ, or microRNAs may also regulate CYP7A1 and ABCA1 transcription and be responsible for the cholesterol homeostasis (Davalos & Fernandez-Hernando, 2013;Fu, Cui, & Klaassen, 2014;Tu, Moss-Pierce, Ford, & Jiang, 2013).…”
mentioning
confidence: 94%